Digitalisasi Manajemen Sistem Dokumen Pengelolaan Perpustakaan Universitas Bumigora Menggunakan Teknologi Radio Frequency Identification (RFID) - Hayati, Ridha Nurul; Saputra, Sahdan; Anggraini, Rini (Universitas Bumigora, 2023)
Bumigora University developed a web-based library information and data processing system, while the contents of the development of the system were only limited to a single information system in which only admin operators handled the system without any direct interaction with library users, while in the analysis and development of the library system only limited to acquisition and return transactions with a system without involving library human resources, but there are problems that are still often encountered in the management of a library at Bumigora University, there is no guarantee of book safety in the library and the work system of library human resources is not yet optimal. Based on this, a Wireless RFID (Radio Frequency Identification) Technology device is needed. This technology supports the identification of book library reshelving, book libraries, book returns with self-service which is expected to provide more accurate information, improve future library services in addition to complementing security aspects. The purpose of this study is to describe the opportunities for Wireless RFID (Radio Frequency Identification) technology to be applied in the Bumigora University library. This study uses an explanatory theory that must be built by researchers based on general data in observations that must be analyzed, explained and interpreted, and uses qualitative methods. The results show that the use of RFID technology in libraries applies both to university libraries, regional libraries, school libraries and others. The use of RFID by Higher Education Libraries will greatly support the following: a. High Speed ​​Inventory System b. Fast Circulation Process The use of RFID will speed up a borrowing and returning circulation process. Therefore, the application of Wireless RFID (Radio Frequency Identification) Technology in the Bumigora University library is needed to create a safe and professional library management.